ARTIFICIAL INTELLIGENCE: PROMOTING SKILLS IN SECONDARY EDUCATION - Rodriguez Pereda, Alim Elizabeth; Ramirez Vigo, Omar Ali; Linares Grijalva, Karin Dessiré; Rodriguez Santos, Marycarmen (LACCEI, 2025)
This systematic literature review (RSL) investigates Artificial Intelligence (AI) as a tool to enhance the development of skills in high school students. The effectiveness of AI-based teaching strategies compared to traditional methods and the importance of skills such as critical thinking, problem solving and creativity were analyzed. A comprehensive literature review was conducted in Scopus using the PRISMA methodology, identifying 45 relevant articles. The results indicate that AI improves the development of key competencies and allows personalization of learning adapted to individual needs. Therefore, AI can contribute significantly to the academic growth and comprehensive development of students, and the need to continue researching these approaches in diverse educational contexts is highlighted.